Analysis of traditional physical therapy programs after myocardial infarction using evidence-based medicine approaches - Khvesyk , Larysa; Antonova-Rafi , Yuliia (The Ukrainian Scientific Medical Youth Journal, 2024)
myocardial infarction is heart muscle necrosis associated with coronary blood supply disorders, which occurs in the vast majority of cases as a result of atherothrombosis. Mechanical revascularization of the myocardium is a more effective and safer way to improve the condition of patients with myocardial infarction compared to long-term drug therapy, but the risk of early complications of cardiac surgery remains high. Considering this, non-pharmacological methods of treatment of myocardial infarction play a valuable role. Numerous publications testify to the fact that in everyday medical practice insufficient attention is paid to the issues of recovery treatment of patients with myocardial infarction after discharge from the hospital. The methods of physical therapy, diet therapy, and psychological adaptation are underestimated. Despite this, a rational way to improve the quality of medical care for patients after a myocardial infarction, as well as to prevent or minimize the occurrence of complications as a result of an acute myocardial infarction, is to improve physical therapy by finding and analyzing the effectiveness of existing physical therapy programs after a myocardial infarction using evidence-based medicine approaches. In this study, groups of patients who suffered a myocardial infarction and underwent various physical therapy programs were studied. In order to evaluate the effectiveness of physical therapy programs for patients after a myocardial infarction, an empirical study was conducted, in which 10 patients who suffered a myocardial infarction and were in the recovery phase, and who were observed at the State Institution «Heart Institute of the Ministry of Health». The following methods of physical therapy were used: therapeutic exercises, dosed walking, respiratory gymnastics, therapeutic gymnastics, massage. In the course of solving the tasks of the work, the effectiveness of individual and complex approaches in building individual programs of physical therapy for patients who suffered a myocardial infarction was revealed and proven. Attention is focused on the fact that compared to the use of group programs, an individual approach in the physical therapy program allows avoiding possible adverse results for each patient who has suffered a myocardial infarction.